Selection bias in historical housing data - Rowena Gray (Queen's University Centre for Economic History (QUCEH), 2018)
A new sample containing rental price and characteristic data for over 15,000 New York City units was collected from historical newspapers for the period 1880 to 1910. These units were geolocated to the historical map of Manhattan Island to explore their geographic coverage, using Geographic Information System (GIS) software. This paper presents the new sample and discusses its representativeness of the New York City housing market during the sample period, with reference to the (limited) previous measures available in the literature and an analysis of the summary statistics of various subsamples of the data which can highlight selection biases. Finally, an analysis of the social status and ethnic composition of individuals located in the sample units in Census year 1880 is presented. Understanding the biases that might be present in this new sample will inform its usefulness in uncovering the workings of historical housing markets and in contributing to the scarce available information on historical housing costs.
Keywords: J15; R31; N91; 330; real estate markets; historical house rental price data; selection bias; US economic history; New York City; historical GIS